2021
DOI: 10.3390/foods10040730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breed Purity and Rearing Systems on the Stability of Sliced Iberian Dry-Cured Ham Stored in Modified Atmosphere and Vacuum Packaging

Abstract: The long-term storage stability of three quality categories of sliced Iberian dry-cured ham defined by the Spanish Iberian Quality Standard (Black, purebred Iberian reared outdoors in Montanera system; Red, Iberian × Duroc crossed (50%) pigs reared outdoors in Montanera system;, and White, Iberian × Duroc crossed (50%) pigs commercially fed) and packaged under vacuum and modified atmosphere packaging (MAP) was studied. Commercial category affected the shelf life, being Black and Red presented the highest lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
2
13
1
1
Order By: Relevance
“…More specifically, the main absorption dominated bands were observed around 1090 and 1270 nm, which would be associated with behavior to the C-H bonds, which is related to fatty acids and alpha and gamma tocopherols [22,23]. Therefore, the overlapping of spectra from Black and Red categories would support the similarity in the fatty acid profile (38.1 and 38.6 g per 100 g of fatty acid methyl esters (% FAMEs) of saturated fatty acids, 54.8 and 54.5% FAMEs of monounsaturated fatty acids and 7.2 and 6.8% FAMES of polyunsaturated fatty acids for Black and Red categories, respectively), and tocopherols content (14.4 and 13.9 µg/g of alpha tocopherol and 1.7 and 1.6 µg/g of gamma tocopherol for Black and Red categories, respectively) between Iberian chorizo manufactured from meat and fat belonging to these two categories, as has been previously reported [8] and as has been also demonstrated in other Iberian dry-cured products [24,25]. This could be mainly explained by the same feeding regime of animals reared under the requirements of both Black and Red categories.…”
Section: Discussionsupporting
confidence: 82%
“…More specifically, the main absorption dominated bands were observed around 1090 and 1270 nm, which would be associated with behavior to the C-H bonds, which is related to fatty acids and alpha and gamma tocopherols [22,23]. Therefore, the overlapping of spectra from Black and Red categories would support the similarity in the fatty acid profile (38.1 and 38.6 g per 100 g of fatty acid methyl esters (% FAMEs) of saturated fatty acids, 54.8 and 54.5% FAMEs of monounsaturated fatty acids and 7.2 and 6.8% FAMES of polyunsaturated fatty acids for Black and Red categories, respectively), and tocopherols content (14.4 and 13.9 µg/g of alpha tocopherol and 1.7 and 1.6 µg/g of gamma tocopherol for Black and Red categories, respectively) between Iberian chorizo manufactured from meat and fat belonging to these two categories, as has been previously reported [8] and as has been also demonstrated in other Iberian dry-cured products [24,25]. This could be mainly explained by the same feeding regime of animals reared under the requirements of both Black and Red categories.…”
Section: Discussionsupporting
confidence: 82%
“…However, color is affected by many factors such as spices added, packaging or processing [ 48 ]. Changes in color parameters have been studied in dry ham [ 40 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that the panelists preferred the group with the lowest concentration of saffron ( Figure 2 ). Other studies [ 52 , 76 ] that indicated the acceptability of dry-cured ham during storage obtained lower scores with storage time, owing to increasing rancid odor and flavor in vacuum-packed ham [ 50 , 51 , 77 ]. Despite the fact the shelf life assigned to Spanish dry-cured ham is approximately one year, this is significantly reduced when the dry-cured ham is sliced and vacuum-packaged [ 51 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations